ENDOCRINE DYNAMICS AND METABOLIC TOXICITY OF GLUCOCORTICOID PHARMACOTHERAPY: OPTIMIZING TAPERING PROTOCOLS IN SYSTEMIC AUTOIMMUNE EXACERBATIONS (World Bulletin of Public Health, 2026)
The potent immunosuppressive and anti-inflammatory properties of exogenous glucocorticoids are inextricably linked to severe, dose-dependent systemic toxicity, primarily manifesting as hypothalamic-pituitary-adrenal axis suppression and iatrogenic metabolic syndrome. This study evaluates the precise clinical efficacy, endocrine preservation, and metabolic outcomes of utilizing a rapid-tapering glucocorticoid bridge protocol compared to conventional, prolonged step-down therapy. A prospective observational cohort study was conducted involving 142 adult patients diagnosed with acute exacerbations of severe rheumatoid arthritis requiring immediate systemic corticosteroid intervention. Subjects were stratified into two clinical pathways: a conventional prolonged therapy cohort (n=68) receiving a standard, slow prednisone taper over 24 weeks, and a targeted rapid-taper cohort (n=74) achieving complete glucocorticoid cessation within 8 weeks, heavily bridged with early disease-modifying antirheumatic drugs. Clinical data indicate that extended receptor occupation by synthetic corticosteroids aggressively paralyses endogenous endocrine function while driving massive hepatic gluconeogenesis. The targeted rapid-taper cohort demonstrated an equivalent rate of clinical remission, maintaining a mean Disease Activity Score-28 of 2.9 ± 0.4 by week 24, but successfully preserved intrinsic adrenal function, evidenced by normal morning serum cortisol levels averaging 14.1 ± 2.2 mcg/dL. Conversely, the conventional group exhibited profound endocrine suppression, with morning cortisol plummeting to 5.2 ± 1.6 mcg/dL (p < 0.001), alongside a 28.3% incidence of clinically significant hyperglycemia. The dynamics of the observed results suggest that the historical paradigm of prolonged, cautious steroid weaning induces unacceptable metabolic collateral damage. Comprehensive pharmacotherapy must actively integrate aggressive, rapid dose deescalation protocols matched with potent steroid-sparing agents to halt acute inflammatory cascades without subjecting the patient to irreversible secondary adrenal insufficiency and progressive osteopenia.
Keywords: Clinical pharmacology; glucocorticoids; hypothalamic-pituitary-adrenal axis